Exploratory analysis of tumor imaging in a Phase 2 trial with cabozantinib in gastrointestinal stromal tumor: lessons learned from study EORTC STBSG 1317 'CaboGIST'. (3rd June 2022) - Kyriazoglou, Anastasios; Jespers, Pieter; Vandecavaye, Vincent; Mir, Olivier; Kasper, Bernd; Papai, Zsuzsanna; Blay, Jean-Yves; Italiano, Antoine; Zaffaroni, Facundo; Litière, Saskia; Nzokirantevye, Axelle; Schöffski, Patrick
Abstract: Background: Gastrointestinal stromal tumors (GISTs) are malignant mesenchymal tumors arising in the gastrointestinal tract. Their systemic treatment is based on the use of tyrosine kinase inhibitors (TKIs) with imatinib, sunitinib, and regorafenib being the preferred agents. Assessment of tumor response to TKI treatment in GISTs is traditionally done according the Response Evaluation Criteria in Solid Tumors (RECIST), while Choi criteria have also been proposed as alternative tool assessing both volumetric and density changes on computer tomography (CT) scans. EORTC STBSG 1317 'CaboGIST' was a single-arm prospective Phase 2 trial which met its primary endpoint, as 60% of patients previously treated with imatinib and sunitinib were progression-free at 12 weeks (95% CI 45–74%) based on local RECIST assessment. Materials and methods: We report here an exploratory analysis of local versus central RECIST version 1.1 assessment and a comparison of RECIST version 1.1 versus Choi criteria. Results: Comparisons between local and central RECIST version 1.1 at week 12 revealed discrepancies in 17/43 evaluable cases (39.5%). When comparing Choi with local and central RECIST version 1.1, discrepancies were observed in 27/43 (62.8%) and 21/43 (48.8%) cases, respectively. A total of 68% of evaluable patients were progression-free and alive at week 12 based on local RECIST, 84% according to central RECIST analysis and 81% when applying Choi criteria. Central assessment upgraded the treatment response both with RECIST version 1.1 and Choi. Conclusions: The results of this exploratory analysis support the conclusion that cabozantinib is active in patients with metastatic or recurrent GIST after treatment with imatinib and sunitinib and confirm once again the limitations of RECIST to capture response to TKI in GIST, and the importance to include density changes in the response evaluation in this setting. Clinical trial number: EORTC 1317, NCT02216578